The Land of Opportunity? Social Class, Returns to Migration, and Occupational Mobility of Swedish Immigrants, 1880–1910 - Castillo, Marcos ; 0009-0006-5263-0946 (European Review of Economic History, 2025)
I study the economic returns to migration among Swedish immigrants in the United States in 1900 and 1910, by social class. Using linked data from full-count Swedish and US censuses via the Swedish Emigrant Register, I first estimate the rates of return to migration using two identification strategies, with the returns exceeding 60 percent, notably higher for migrants from lower social classes. Furthermore, most migrants did not experience substantial occupational upgrade compared to their brothers in Sweden, which suggests that while migration yielded sizeable economic returns, they were primarily due to higher US wages rather than occupational mobility.